A think-aloud study : L2 reading strategies used by higher and lower proficiency Thai EFL readers - Kamlaitip Pattapong, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aims to explore the complex phenomenon hidden in Thai EFL students’ minds and to detect the different strategies used by two groups of readers with different levels of L2 reading proficiency whilst reading four English reading texts through think-aloud activities. Eight undergraduate students (two groups of four high scorers and four low scorers) were selected from thirty-six students to participate in think-aloud activities and retrospective interview programmes. Verbal reports from the think-aloud and retrospective interviews were transcribed and contentanalysed. The analysis of the frequencies of strategies used found similar uses of strategies among both groups of different L2 reading proficiency. Despite the similar uses of strategies among both groups, the qualitative analysis revealed a more efficient use of higher-order level strategies reported by the group of highly proficient readers. Further, the qualitative analysis opportunistically allowed a closer look at the reading strategies used for two text types: narrative and expository.